Diels–Alder Additions to 2, 2'‐Biaceanthrylene. Issue 2 (5th January 2023) - Du, Yachu; Pandey, Krishna; Plunkett, Kyle N.
Abstract: A series of Diels–Alder reactions between the diene 2, 2'‐biaceanthrylene and several dienophiles is presented. The diene is a cyclopenta‐fused polycyclic aromatic hydrocarbon with anthracene units linked by two cyclopentene rings. Depending on the dienophile, the major product was the result of a single addition (dimethyl acetylenedicarboxylate) or double addition (quinone, benzyne) to the diene. Single crystal X‐ray analysis of the quinone‐derivative shows a propeller‐like structure composed of mixed enantiomers. The synthesis and photophysical properties of these compounds are presented. Abstract :